2018
DOI: 10.1186/s12885-018-4484-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased systemic zonula occludens 1 associated with inflammation and independent biomarker in patients with hepatocellular carcinoma

Abstract: BackgroundHepatocellular carcinoma (HCC) is a frequent type of primary liver cancer, and its prevalence is increasing worldwide. Indeed, the underlying molecular mechanism is not well understood. Previous studies have shown evidence that tight junction (TJ) components were correlated with carcinogenesis and tumor development. Our aims were to determine the serum levels of tight junction protein Zonula Occludens (ZO)-1 and an inflammatory marker such as high-sensitive C-reactive protein (hs-CRP) in HCC patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 32 publications
(46 reference statements)
0
25
0
Order By: Relevance
“…Similarly, although occludin -/- mice exhibited no gross anatomical defects, the gastric epithelial cells became hyperplastic after 40 wk[ 19 ]. Of note, our human study in HCC patients indicated a significant correlation between hepatic ZO-1 and high-sensitive C-reactive protein, however, the causal relationship remains unclear[ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, although occludin -/- mice exhibited no gross anatomical defects, the gastric epithelial cells became hyperplastic after 40 wk[ 19 ]. Of note, our human study in HCC patients indicated a significant correlation between hepatic ZO-1 and high-sensitive C-reactive protein, however, the causal relationship remains unclear[ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we found increased systemic ZO-1 level in HCC patients reflecting increased intestinal permeability [31]. Moreover, plasma ZO-1 level was positively correlated with the inflammatory marker hs-CRP and with disease severity, suggesting inflammation drives intestinal permeability associated with HCC progression [31]. Bacterial overgrowth leads to increased production of pro-inflammatory cytokines such as TNF-α, IL-6, and IL-1β, which is mainly mediated through the TLR4-NF-kB signaling pathway, thereby promoting intestinal inflammation and HCC progression [19].…”
Section: Intestinal Epithelial Barrier Dysfunction: Role Of Tight Junmentioning
confidence: 82%
“…Growing evidence suggests that inflammation and TJ protein disruption are two of the key players driving increased intestinal permeability. In our previous study, we found increased systemic ZO-1 level in HCC patients reflecting increased intestinal permeability [31]. Moreover, plasma ZO-1 level was positively correlated with the inflammatory marker hs-CRP and with disease severity, suggesting inflammation drives intestinal permeability associated with HCC progression [31].…”
Section: Intestinal Epithelial Barrier Dysfunction: Role Of Tight Junmentioning
confidence: 94%
“…Some studies have reported that tight junction ZO-1 protein was related to some diseases and could be used as an inflammatory marker. Ram et al reported that the systemic concentration of ZO-1 was significantly elevated in hepatocellular carcinoma patients and was positively correlated with inflammatory markers [32]. Meanwhile, Boer at el.…”
Section: Discussionmentioning
confidence: 98%